ANALISA PERTUMBUHAN PENYALURAN KUR PADA UMKM DALAM RANGKA PENURUNAN ANGKA KEMISKINAN DI INDONESIA - Ibrahim Hasan (Jurnal Ilmiah Mahasiswa FEB, 2015)
Poverty is a classical problem that becomes a question of almost all countries and Indonesia is one of them. One alternative to reduce poverty can be through the MSME sector. This research purpose to analyze the growth of KUR distribution to MSME in the effort of poverty reduction in Indonesia. Data used from secondary data that yearly published by Badan Pusat Statistik, Bank Indonesia, Kementerian UMKM dan Koperasi, and Komite-KUR. Data analysis method who used in this research are error correction model (ECM). Based on the results of research, variable KUR distribution and MSME GDP have the negative impact on poverty in the long term, and MSME GDP and business unit MSME have the negative impact on poverty in the short term . A variable that has negative impact on poverty either in the short-term and long-term is  variable MSME GDP.Keyword: kemiskinan, UMKM, KUR